Methodological conditions of implementation of educational progress monitoring in the process of future land surveyors professional training - IVANIUTA, Oleksiy; KUBITCKIY, Sergiy (Journal of Education, Technology and Computer Science, 2013)
The paper analyzed the essence of monitoring learning achievement of students as educational technology; based on analysis selected and justified methodological conditions of implementation of monitoring learning achievement in process of professional training of future land surveyors